On Motion Planning for Point-to-Point Maneuvers for a Class of Sailing Vehicles - Lin Xiao; Jerome Jouffroy (Journal of Control Science and Engineering)
Despite their interesting dynamic and controllability properties, sailing vehicles have not been much studied in the control community. In this paper, we investigate motion planning of such vehicles. Starting from a simple dynamic model of sailing vessels in one dimension, this paper first considers their associated controllability issues, with the so-called no-sailing zone as a starting point, and it links them with a motion planning strategy using two-point boundary value problems as the main mathematical tool. This perspective is then expanded to do point-to-point maneuvers of sailing vehicles in the plane, that is, automatic path generation combined with computation of control input profiles. Simulations are presented to illustrate the potential of the approach.